2008
DOI: 10.1007/s00253-008-1404-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of microbial adhesion and biofilm growth using electrochemical impedancemetry

Abstract: Electrochemical impedance spectroscopy was tested to monitor the cell attachment and the biofilm proliferation in order to identify characteristic events induced on the metal surface by Gram-negative (Pseudomonas aeruginosa PAO1) and Gram-positive (Bacillus subtilis) bacteria strains. Electrochemical impedance spectra of AISI 304 electrodes during cell attachment and initial biofilm growth for both strains were obtained. It can be observed that the resistance increases gradually with the culture time and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 26 publications
2
36
0
1
Order By: Relevance
“…Modeling studies have predicted that the conductivity of the biofilm would have to be 10 À4 mS cm À1 to avoid electron transfer limitation (Marcus et al, 2007). Although biofilms are generally considered to act as insulators rather than conductors (Herbert-Guillou et al, 1999;Muñ ozBerbel et al, 2006;Dheilly et al, 2008), the finding that cells at substantial distance from the anode are metabolically active is consisent with the concept that anode biofilms may be conductive. Clearly, the more cells that can release electrons from metabolic activity, the greater the potential current output.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies have predicted that the conductivity of the biofilm would have to be 10 À4 mS cm À1 to avoid electron transfer limitation (Marcus et al, 2007). Although biofilms are generally considered to act as insulators rather than conductors (Herbert-Guillou et al, 1999;Muñ ozBerbel et al, 2006;Dheilly et al, 2008), the finding that cells at substantial distance from the anode are metabolically active is consisent with the concept that anode biofilms may be conductive. Clearly, the more cells that can release electrons from metabolic activity, the greater the potential current output.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies have also predicted that high current production by a thick anode associated biofilm is only feasible if the bacterial biofilm is conductive [118,119]. The production of a conductive biofilm is highly unusual as most biofilms act as insulators [120][121][122]. A major breakthrough in the field would be the measurement and determination of the conductivity, and the components responsible of conductivity, of a bacterial biofilm in a MFC.…”
Section: Electrical Interactions Between Microbes and Electrodesmentioning
confidence: 99%
“…Among the various techniques, electrochemical sensors (Tribollet 2003) have shown promise in the detection of very small changes in the interfacial metal-solution properties, for instance the interfacial capacitance. Studies have demonstrated that this parameter is sensitive to the bacterial attachment and colonization of sensor surfaces from the initial attachment until the formation of mature biofilms (Munoz-Berbel et al 2007;Dheilly et al 2008). However, greater effort is still required to characterize different electrochemical signals more fully and to miniaturize the sensors and/or sensor arrays.…”
Section: (B) Biofilm Monitoringmentioning
confidence: 99%